Deformation process of aluminum oxide dispersion strengthened copper-based composite material

By adopting a combination process of small extrusion specific hot extrusion and small deformation amount rotary forging in alumina diffusion reinforced copper-based composite materials, the problem of low yield while maintaining high mechanical and electrical conductivity is solved, and high efficiency is achieved Production of finished products.

CN119457073APending Publication Date: 2025-02-18HENAN UNIV OF SCI & TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411862467.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The prior art is difficult to improve product yield while maintaining the high mechanical properties and electrical conductivity of alumina diffusion reinforced copper-based composite materials, and the hot extrusion process with a high extrusion ratio is prone to cause material cracking and reduce the yield.

Method used

Using a combination deformation process of hot extrusion with a small extrusion ratio (3~10:1) and rotary forging with small deformation amount, gradually densify the material, reduce deformation resistance, reduce cracking risk, and realize the material through multi-pass rotary forging efficient forming.

Benefits of technology

While maintaining high mechanical properties and conductive properties, the product yield is significantly improved, resource waste and energy consumption are reduced, and production costs are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention belongs to the technical field of composite material preparation and processing, and particularly relates to a deformation process of an aluminum oxide dispersion strengthened copper-based composite material. The deformation process of the aluminum oxide dispersion strengthened copper-based composite material comprises the following steps: carrying out hot extrusion on a sintered blank for preparing the aluminum oxide dispersion strengthened copper-based composite material, and then carrying out rotary swaging at room temperature; the temperature of hot extrusion is 900-950 DEG C, and the extrusion ratio during hot extrusion is (3-10): 1; and the single-pass rolling reduction of the rotary forging is 0.2-2 mm. By selecting a combined deformation process of hot extrusion with a smaller extrusion ratio and rotary swaging with small deformation amount, the material is partially densified through hot extrusion, and then is further densified through subsequent rotary swaging, so that the deformation resistance of the material is small, the cracking condition during hot extrusion can be greatly reduced, the yield of a product is improved, and meanwhile, higher mechanical property and conductivity are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite material preparation and processing, and in particular to a deformation process of an aluminum oxide dispersion-strengthened copper-based composite material. Background Art

[0002] Difficult-to-deform metals usually refer to metals that are difficult to process by conventional plastic forming methods due to their high yield strength, hardness and low plasticity during plastic deformation. At present, the processing technologies for difficult-to-deform metals mainly include hot extrusion, hot rolling, hot forging, etc. However, these traditional processes often have problems such as uneven deformation, decreased material properties, high energy consumption and high cost during processing.

[0003] Al2O3 / Cu composite material is a material that introduces nano-scale Al2O3 particles with good thermal stability, high hardness and dispersed distribution into the copper matrix, so that the material maintains high strength and high conductivity while having excellent high-temperature mechanical properties. It has broad application prospects in the fields of electromagnetic rail guns, resistance welding electrodes, high-voltage contact switches, etc. However, due to its high hardness and high strength, it is a typical difficult-to-deform metal. A single traditional processing method is often difficult to obtain the ideal deformation effect and material properties, which to a certain extent limits its use as a key component.

[0004] At present, the deformation method of Al2O3 / Cu composite materials is to hot extrude, draw or forge the sintered blank. However, studies have shown that when the small extrusion ratio λ is 2.25:1, the mechanical properties of the composite material are not improved but lower than those of the cast state. Therefore, in order to improve the density of the material and ensure the mechanical properties of the material, the extrusion ratio is required to be not less than 10:1 when the sintered blank is extruded, generally 10~30:1. However, in actual production, it is found that a higher extrusion ratio leads to a significant increase in the probability of cracking of the composite material, which reduces the product yield, causes serious waste of resources, and increases production costs. Summary of the invention

[0005] The present invention provides a deformation process for an alumina dispersion-strengthened copper-based composite material, which solves the problem that the existing deformation process cannot improve the product yield while maintaining relatively high mechanical properties and electrical conductivity.

[0006] In order to solve the above technical problems, the technical solution of the deformation process of the alumina dispersion strengthened copper-based composite material of the present invention is: A deformation process for an alumina dispersion strengthened copper-based composite material comprises the following steps: hot extruding a sintered blank for preparing the alumina dispersion strengthened copper-based composite material, and then rotary forging at room temperature; the hot extrusion temperature is 900-950°C, the extrusion ratio during hot extrusion is (3-10):1; the single-pass reduction amount of the rotary forging is 0.2-2 mm.

[0007] The beneficial effects of the present invention are as follows: the present invention improves the prior art and provides a deformation process for an alumina dispersion-strengthened copper-based composite material. By selecting a combined deformation process of hot extrusion with a relatively small extrusion ratio and rotary forging with a small deformation amount, the hot extrusion partially densifies the material, and then further densifies the material through subsequent rotary forging. The material has a small deformation resistance, can greatly reduce cracking during hot extrusion, and improve the yield of the product. Through the combined deformation process of hot extrusion and rotary forging, the alumina dispersion-strengthened copper-based composite material can also achieve higher mechanical properties and electrical conductivity.

[0008] The alumina dispersion strengthened copper-based composite material prepared by the present invention has an electrical conductivity of ≥80% IACS, a room temperature hardness of ≥160HB, and a tensile strength of ≥550MPa, and improves the product yield while maintaining relatively high mechanical properties and electrical conductivity, thereby reducing resource waste, energy consumption, and costs.

[0009] In order to further improve the mechanical properties of the composite material, preferably, the spindle speed during the rotary forging is 200-300 r / min, and the axial feed rate is 5-11 mm / s.

[0010] In order to further enable the composite material to deform uniformly during the extrusion process, preferably, the extrusion speed during the hot extrusion is 5-15 mm / s. More preferably, the extrusion ratio during the hot extrusion is 2:1 and the extrusion speed is 10 mm / s.

[0011] In order to further eliminate the internal stress of the material and soften the material, preferably, a heat preservation treatment is performed before the hot extrusion, the temperature of the heat preservation treatment is 900-950° C., and the time of the heat preservation treatment is 1-2 hours.

[0012] In order to further improve the mechanical properties and electrical conductivity of the composite material, preferably, the sintered blank is obtained by pressing, internal oxidation, reduction and sintering of mixed powder, and the mixed powder is a mixture of copper-aluminum alloy powder and Cu2O powder.

[0013] In order to further improve the sintering efficiency of the sintered blank and enhance the strengthening ability of the dispersed phase, preferably, the temperature of the internal oxidation is 850-950°C; the temperature of the reduction is 850-980°C; and the temperature of the sintering is 880-980°C. DETAILED DESCRIPTION

[0014] The technical concept of the deformation process of the alumina dispersion strengthened copper-based composite material of the present invention is as follows: At present, some parts in the field of powder metallurgy need to be deformed on the sintered blanks, and the internal pores are compressed or discharged by plastic deformation to improve the density of the blanks. However, for alumina dispersion-strengthened copper-based composite materials, the introduction of oxide particles increases the deformation resistance of the base metal and reduces the plasticity. For powder materials with poor deformation ability, it is difficult to increase the density.

[0015] In the existing technology, in order to improve the density and mechanical properties, electrical conductivity and thermal conductivity of composite materials, a hot extrusion process with a large extrusion ratio (10~30:1) is generally used for deformation processing of sintered blanks. However, the deformation resistance of hot extrusion with a large extrusion ratio is too large, and the material either cannot be squeezed or cracks, which increases the risk of cracking of the sintered blank during the hot extrusion process and is not conducive to subsequent processing. In addition, the sintered blank cannot be forged directly, and the blank has a large porosity and is prone to cracking.

[0016] The present invention adopts a combined deformation process of hot extrusion with a small extrusion ratio (3-10:1) + rotary forging with a small deformation amount, gradually densifies, reduces the deformation resistance of the material, improves the product yield while maintaining high mechanical properties and conductive properties, reduces resource waste, reduces energy consumption, and reduces costs.

[0017] The deformation process of the alumina dispersion strengthened copper-based composite material of the present invention comprises the following steps: (1) Copper-aluminum alloy powder and Cu2O powder are mixed to obtain a mixed powder, wherein the mass proportion of Cu2O powder in the mixed powder is 2.5-5%, and the aluminum content in the copper-aluminum alloy powder is 0.2-1%. The mixed powder is pressed and then internally oxidized at 850-950°C, then reduced at 850-980°C, and then sintered at 880-980°C to obtain a sintered blank.

[0018] (2) The sintered blank is first heat-treated at 900-950°C for 1-2 hours, and then hot-extruded at 900-950°C with an extrusion ratio of (3-10):1 and an extrusion speed of 5-15 mm / s to obtain a dispersed copper rod.

[0019] (3) The dispersed copper rod obtained by hot extrusion in step (2) is subjected to multiple passes of rotary forging at room temperature, wherein the spindle speed during rotary forging is 200-300 r / min, the axial feed rate is 5-11 mm / s, the reduction amount per pass is 0.2-2 mm, and the total deformation during rotary forging is 50-80%.

[0020] In a specific embodiment, the heat preservation treatment is carried out in a heating furnace, and the hot extrusion is carried out in a high-precision hot extruder to ensure the temperature and pressure control accuracy during the extrusion process. The sintered blank is first placed in a heating furnace for heat preservation to eliminate internal stress and soften the material; then placed in the die of the extruder, and pressure is applied for extrusion deformation. During the hot extrusion process, the initial shape and size of the material are determined by adjusting the extrusion speed and extrusion ratio.

[0021] In a specific embodiment, the rotary forging is performed in a high-precision rotary forging machine to ensure accurate control of parameters such as rotation speed, feed rate and forging pressure during the forging process. The rotary forging adopts multiple passes of rotary forging, and the pressing amount of each pass is 0.2~0.5mm. The composite material after hot extrusion is placed in the rotary forging equipment, and the composite material is deformed by multiple passes with small deformation through the rotation and feeding of the rotary wheel. During the rotary forging process, the precise forming and performance optimization of the material are achieved by adjusting the rotation speed, feed rate and pressing amount.

[0022] In a specific embodiment, the annealing is carried out in a high-precision annealing furnace to ensure the temperature and time control accuracy during the annealing process to avoid oxidation, deformation or performance degradation of the product due to excessive temperature or excessive time. The composite material after rotary forging is placed in the heating zone of the annealing furnace to ensure that there is an appropriate gap between the products to ensure that the heat can be evenly transferred; at the same time, the cleanliness and sealing of the furnace are checked to prevent the intrusion of impurities and oxygen. After the insulation is completed, it is cooled with the furnace to prevent it from deformation or cracking.

[0023] In a specific embodiment, after annealing is completed, the composite material is taken out of the annealing furnace and necessary cleaning and inspection are performed. The surface quality and dimensional accuracy of the product are checked to ensure that it meets the design requirements.

[0024] The implementation manner of the present invention is further described below in conjunction with specific examples.

[0025] 1. Specific embodiment of the deformation process of the alumina dispersion strengthened copper-based composite material of the present invention Example 1 The deformation process of the alumina dispersion strengthened copper-based composite material of this embodiment is as follows: (1) Mixed powder charging: Take the following raw materials: Cu-Al alloy powder produced by water mist method, with an aluminum content of 0.2wt% and a particle size of 45μm; the oxidant is Cu2O powder, with a particle size of 50-100μm and a purity of ≥99.5%; mix the Cu-Al alloy powder and Cu2O to obtain a mixed powder, the weight of the mixed powder is about 700g, the content of Cu2O in the mixed powder is 2.5wt%, and the remainder is Cu-Al alloy powder; (2) Internal oxidation reduction and sintering: The mixed powder is pressed to obtain an isostatically pressed billet, which is then placed in a furnace. Nitrogen is introduced to exhaust the air, and the nitrogen pressure is maintained at about 3 atm. The temperature is raised for internal oxidation at 950°C for 2 hours. After the internal oxidation is completed, hydrogen is introduced to exhaust the nitrogen, and the hydrogen pressure is maintained at about 3 atm. Reduction is performed under the reduction process parameters at a temperature of 980°C for 2 hours. After the reduction is completed, the temperature is raised for sintering at a temperature of 980°C for 2 hours. After sintering is completed, the temperature is lowered to obtain a sintered billet.

[0026] (3) Hot extrusion: The sintered billet was first placed in a heating furnace at 950°C for 1 h, and then hot extruded at 950°C on a horizontal extruder with an extrusion ratio of 5:1 and an extrusion speed of 15 mm / s to obtain a dispersed copper rod.

[0027] (4) Rotary forging: The dispersed copper bar obtained by hot extrusion in step (3) is placed in a rotary forging device and subjected to multiple passes of rotary forging at room temperature. The spindle speed during rotary forging is 300 r / min, the axial feed rate is 11 mm / s, the reduction amount per pass is 0.2 mm, and the total deformation amount of rotary forging (referring to the deformation amount of the cross section of the bar) is 60%.

[0028] Example 2 The deformation process of the alumina dispersion strengthened copper-based composite material of this embodiment is as follows: (1) Mixed powder charging: Take the following raw materials: Cu-Al alloy powder produced by water mist method, with an aluminum content of 0.2wt% and a particle size of 45μm; the oxidant is Cu2O powder, with a particle size of 50-100μm and a purity of ≥99.5%; mix the Cu-Al alloy powder and Cu2O to obtain a mixed powder, the weight of the mixed powder is about 700g, the content of Cu2O in the mixed powder is 2.5wt%, and the remainder is Cu-Al alloy powder; (2) Internal oxidation reduction and sintering: The mixed powder is pressed to obtain an isostatically pressed billet, which is then placed in a furnace. Nitrogen is introduced to exhaust the air, and the nitrogen pressure is maintained at about 3 atm. The temperature is raised for internal oxidation at 950°C for 2 hours. After the internal oxidation is completed, hydrogen is introduced to exhaust the nitrogen, and the hydrogen pressure is maintained at about 3 atm. Reduction is performed under the reduction process parameters at a temperature of 980°C for 2 hours. After the reduction is completed, the temperature is raised for sintering at a temperature of 980°C for 2 hours. After sintering is completed, the temperature is lowered to obtain a sintered billet.

[0029] (3) Hot extrusion: The sintered billet was first placed in a heating furnace at 950°C for 1 h, and then hot extruded at 950°C on a horizontal extruder with an extrusion ratio of 8:1 and an extrusion speed of 15 mm / s to obtain a dispersed copper rod.

[0030] (4) Rotary forging: The dispersed copper bar obtained by hot extrusion in step (3) is placed on a rotary forging device and subjected to multiple passes of rotary forging at room temperature. The spindle speed during rotary forging is 300 r / min, the axial feed rate is 10 mm / s, the reduction amount per pass is 2 mm, and the total deformation amount of rotary forging is 80%.

[0031] Example 3 The deformation process of the alumina dispersion strengthened copper-based composite material of this embodiment is as follows: (1) Mixed powder charging: Take the following raw materials: Cu-Al alloy powder produced by water mist method, with an aluminum content of 0.2wt% and a particle size of 45μm; the oxidant is Cu2O powder, with a particle size of 50-100μm and a purity of ≥99.5%; mix the Cu-Al alloy powder and Cu2O to obtain a mixed powder, the weight of the mixed powder is about 700g, the content of Cu2O in the mixed powder is 2.5wt%, and the remainder is Cu-Al alloy powder; (2) Internal oxidation reduction and sintering: The mixed powder is pressed to obtain an isostatically pressed billet, which is then placed in a furnace. Nitrogen is introduced to exhaust the air, and the nitrogen pressure is maintained at about 3 atm. The temperature is raised for internal oxidation at 950°C for 2 hours. After the internal oxidation is completed, hydrogen is introduced to exhaust the nitrogen, and the hydrogen pressure is maintained at about 3 atm. Reduction is performed under the reduction process parameters at a temperature of 980°C for 2 hours. After the reduction is completed, the temperature is raised for sintering at a temperature of 980°C for 2 hours. After sintering is completed, the temperature is lowered to obtain a sintered billet.

[0032] (3) Hot extrusion: The sintered billet was first placed in a heating furnace at 950°C for 1 h, and then hot extruded at 950°C on a horizontal extruder with an extrusion ratio of 10:1 and an extrusion speed of 15 mm / s to obtain a dispersed copper rod.

[0033] (4) Rotary forging: The dispersed copper bar obtained by hot extrusion in step (3) is placed on a rotary forging device and subjected to multiple passes of rotary forging at room temperature. The spindle speed during rotary forging is 200 r / min, the axial feed rate is 5 mm / s, the reduction amount per pass is 1 mm, and the total deformation amount of rotary forging is 70%.

[0034] 2. Comparison Comparative Example 1 The deformation process of the alumina dispersion strengthened copper-based composite material of this comparative example is as follows: (1) Mixed powder charging: Take the following raw materials: Cu-Al alloy powder produced by water mist method, with an aluminum content of 0.2wt% and a particle size of 45μm; the oxidant is Cu2O powder, with a particle size of 50-100μm and a purity of ≥99.5%; mix the Cu-Al alloy powder and Cu2O to obtain a mixed powder, the weight of the mixed powder is about 700g, the content of Cu2O in the mixed powder is 2.5wt%, and the remainder is Cu-Al alloy powder; (2) Internal oxidation reduction and sintering: The mixed powder is pressed to obtain an isostatically pressed billet, which is then placed in a furnace, and nitrogen is introduced to exhaust the air. The nitrogen pressure is maintained at about 3 atm, and the temperature is raised for internal oxidation. The temperature of the internal oxidation is 900°C, and the holding time is 2 hours. After the internal oxidation is completed, hydrogen is introduced to exhaust the nitrogen, and the hydrogen pressure is maintained at about 3 atm. Reduction is performed under the reduction process parameters at a temperature of 930°C and a holding time of 2 hours. After the reduction is completed, the temperature is continued to be raised for sintering at a temperature of 950°C and a holding time of 2 hours. After sintering is completed, the temperature is lowered to obtain a sintered billet.

[0035] (3) Hot extrusion: The sintered blank is first placed in a heating furnace at 950°C for 1 hour, and then hot extruded at 950°C on a horizontal extruder to increase the density of the sintered blank. The extrusion ratio is 30:1 and the extrusion speed is 15 mm / s to obtain a dispersed copper rod.

[0036] (4) Drawing: The dispersed copper rod obtained by hot extrusion in step (3) is subjected to cold drawing deformation to further improve the mechanical properties. The deformation of the cross section is 30%, reaching the same level of total deformation from the sintered blank to the final product as in Example 2.

[0037] 3. Experimental Examples This experimental example tests the mechanical properties and conductor properties of the alumina dispersion-strengthened copper-based composite material (Al2O3 / Cu) obtained in the embodiment and the comparative example. The specific method is: the conductivity of the sample is tested using a D60K eddy current conductivity meter, the hardness of the sample is tested using a Brinell hardness tester, and the tensile strength and elongation are tested in accordance with GB / T 228-2010 "Room Temperature Test Method for Tensile Test of Metallic Materials". The test results are shown in Table 1.

[0038] Table 1 Performance test results of Al2O3 / Cu composites After deformation and annealing, the Al2O3 / Cu composite material prepared by the present invention has a conductivity of ≥80%IACS, a room temperature hardness of ≥150HB, and a tensile strength of ≥520MPa, and the performance is greatly improved while reducing energy consumption and cost. The deformation process provided by the present invention significantly improves the yield rate: the Al2O3 / Cu composite material is prepared by the process of the comparative example, and 2 samples crack in 5 extrusion experiments; the Al2O3 / Cu composite material is prepared by using Examples 1-3, and 5 samples in each example are successfully prepared without cracking.

[0039] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A deformation process for an alumina dispersion-strengthened copper-based composite material, characterized in that: The method comprises the following steps: hot extruding a sintered blank for preparing an alumina dispersion-strengthened copper-based composite material, and then rotary forging at room temperature; the hot extrusion temperature is 900-950°C, the extrusion ratio during hot extrusion is (3-10):1; the single-pass reduction amount of the rotary forging is 0.2-2 mm.

2. The deformation process of the alumina dispersion strengthened copper-based composite material according to claim 1, characterized in that: The main shaft speed during rotary forging is 200-300 r / min, and the axial feed rate is 5-11 mm / s.

3. The deformation process of the alumina dispersion strengthened copper-based composite material according to claim 1, characterized in that: The extrusion speed during the hot extrusion is 5-15 mm / s.

4. The deformation process of the alumina dispersion strengthened copper-based composite material according to any one of claims 1 to 3, characterized in that: The heat preservation treatment is performed before the hot extrusion, the temperature of the heat preservation treatment is 900-950° C., and the time of the heat preservation treatment is 1-2 hours.

5. The deformation process of the alumina dispersion strengthened copper-based composite material according to claim 1, characterized in that: The sintered blank is obtained by subjecting mixed powder to pressing, internal oxidation, reduction and sintering treatments, and the mixed powder is obtained by mixing copper-aluminum alloy powder and Cu2O powder.

6. The deformation process of the alumina dispersion strengthened copper-based composite material according to claim 5, characterized in that: The temperature of the internal oxidation is 850-950°C; the temperature of the reduction is 850-980°C; and the temperature of the sintering is 880-980°C.